Making Migration Work : The Future of Labour Migration in the European Union - Holtslag, Jan Willem; Kremer, Monique; Schrijvers, Erik (WRR Verkenningen, 2013)
Largely because of the European Union's two-phase expansion in 2004 and 2007, labor migration across the continent has changed significantly in recent years. Notably, the EU's policy of open borders has enabled a growing stream of workers to leave new member states in search of higher wages. As a result, the nature, scale, and direction of migration flows have changed dramatically. Making Migration Work explores how policy can-and should-address these changes. In the process, this timely volume considers the future trajectory of a phenomenon that has become an increasingly sensitive political issue in many European nations.